Improved electrochemical performances by Ni-catecholate-based metal organic framework grown on NiCoAl-layered double hydroxide/multi-wall carbon nanotubes as cathode catalyst in microbial fuel cells. (October 2021) - Chen, Junfeng; Yang, Jiaqi; Jiang, Liting; Wang, Xuemei; Yang, Daoxin; Wei, Qingying; Wang, Yongle; Wang, Renjun; Liu, Yanyan; Yang, Yuewei
Graphical abstract: Highlights: Ni-CAT MOF grown on NiCoAl-LDH/MWCNTs by hydrothermal method. Hybrid decorated MFC cathode has excellent cycle stability and rate performance. Maximum power density produced by MFC was 448.5 ± 12.0 mW/m 2 . Fully exposed active sites and high conductivity improved performance. Abstract: In this study, a simple two-step hydrothermal method was used to prepare the cathode catalyst of the microbial fuel cell (MFC). NiCoAl- layered double hydroxide (LDH) nanosheets were grown vertically on multi-wall carbon nanotubes (MWCNTs) in situ; Ni-catecholate-based metal organic framework (Ni-CAT MOF) were modified on the surface of the nanosheets. The maximum output voltage of Ni-CAT/NiCoAl-LDH/MWCNTs was 475 mV, the maximum stabilization time was 8 d, the maximum output power was 448.5 ± 12.0 mW/m 2, which was 1.03 times that of NiCoAl-LDH/MWCNT-MFC (433.5 ± 14.8 mW/m 2 ) and 1.35 times of NiCoAl-LDH- MFC (329.9 ± 2.9 mW/m 2 ). The layer structure of LDH, conductivity of Ni-CAT and MWCNT improved the flow efficiency of ions between layers and effectively reduced transmission resistance, and these have effectively enhanced the cycle stability and power generation efficiency of the electrode.